EVALUASI MANAJEMEN PEMASARAN PENDIDIKAN BERBASIS MEDIA SOSIAL DALAM MENARIK MINAT PESERTA DIDIK DI SMP AL-MA’RUFIYAH MAGELANG - Iqbal Khairunsyah Putra; Dahlia; Yeny Fitriyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of digital technology and the massive use of social media have encouraged educational institutions to adapt more innovative and competitive educational marketing strategies to attract new students. This study aims to evaluate social media-based educational marketing management in attracting students at SMP Al-Ma'rufiyah Magelang. This study uses a qualitative method with a descriptive-evaluative approach through data collection techniques such as in-depth interviews, observation, and documentation involving school management, the social media team, and relevant stakeholders. The results of the discussion indicate that the use of social media such as Instagram, Facebook, and WhatsApp has become the primary means of conveying school information, building the institution's image, and establishing communication with prospective students and parents. However, the implementation of marketing management still faces limitations in strategic planning, content consistency, and optimization of social media analytics. Research findings reveal that the effectiveness of social media-based educational marketing is greatly influenced by content quality, audience engagement, and the ability of human resources to professionally manage digital platforms. The implications of this research emphasize the importance of strengthening planned, integrated, and sustainable social media-based educational marketing management as a strategic strategy to increase the attractiveness and existence of educational institutions amidst increasingly competitive competition. Keywords: Evaluation, Management, Media, Interest, Education.